Assessment of drought trends in the Upper Ewaso Ng'iro River Basin using the SPI and SPEI - June Jerop Kimaiyo; Bancy Mbura Mati; Joseph Kipyegon Sang; Edwin Kimutai Kanda (Water Practice and Technology, 2023)
Drought assessment is necessary for creating adaptation and resilience measures for the livelihoods of the affected communities. This study assessed drought trends in Kenya's Upper Ewaso Ng'iro River Basin (UENB) from 1981 to 2020. A Standardized Precipitation Index (SPI), a precipitation-based index, and a Standardized Precipitation Evapotranspiration Index (SPEI), a multivariate index that considers the difference between precipitation and potential evapotranspiration (PET), were used to evaluate drought severity and frequency over varying timescales. Monthly rainfall and temperature data for 10 stations within the basin were analyzed to calculate the SPI and SPEI time series values for 3, 6, and 12 months. The results demonstrate an alarming increase in the severity and frequency of drought events in the UENB since 1999. Additionally, the study reveals that the SPI and SPEI indices differ in identifying temporal and spatial drought characteristics, with longer timescales showing improved accuracy. Notably, the SPEI identifies more extensive and severe drought periods in the region compared to the SPI. The research findings are crucial in guiding policy decisions related to SDGs as they provide valuable information on drought trends necessary for implementing effective drought adaptation and resilience measures and promoting sustainable development in the UENB. HIGHLIGHTS The study describes the temporal and spatial evolution characteristics of meteorological drought in the region.; There has been an increase in drought frequency in the basin over the 40 years, and it has significantly increased since 2000.; The study shows the relationship between the SPI and SPEI in identifying drought events and that the SPEI performed better than the SPI in identifying drought.;